UPAYA MENINGKATKAN HASIL BELAJAR PEMBELAJARAN IPA MATERI PERKEMBANGBIAKAN TUMBUHAN SECARA GENERATIF MELALUI MODEL EXAMPLE NON-EXAMPLE DENGAN METODE DIRECT OBSERVASI - Utomo, Rachmat Karno (Jurnal Inovasi Pembelajaran di Sekolah, 2022)
Best Practice learning is learning that aims to find out whether the Example Non-Example Learning Model with the Direct Observation method can improve science learning outcomes in Generative Plant Propagation Material for Class VI Students of the Batak Tribe Semester I SD Negeri Pendrikan Lor 01 2021/2022 Academic Year. The main task of the teacher at school is to carry out the learning process in the classroom, in order to achieve the overall educational goals, namely to form and develop the personality of students and develop scientific potential as a whole. To carry out these basic tasks, teachers need to have broad insight, knowledge, competence, choose the right strategies, methods, models and media in the learning process. The results of this learning best practice show that the use of example non example learning models with the direct observation method can improve science learning outcomes in plant propagation material generatively. Students feel happy in participating in learning, are more active, creative, grow high curiosity, dare to express opinions or ideas, are enthusiastic about doing assignments so that learning outcomes can increase significantly.